2014
DOI: 10.1016/j.ccr.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

A Long Noncoding RNA Activated by TGF-β Promotes the Invasion-Metastasis Cascade in Hepatocellular Carcinoma

Abstract: The role of TGF-β-induced epithelial-mesenchymal transition (EMT) in cancer cell dissemination is well established, but the involvement of lncRNAs in TGF-β signaling is still unknown. In this study, we observed that the lncRNA-activated by TGF-β (lncRNA-ATB) was upregulated in hepatocellular carcinoma (HCC) metastases and associated with poor prognosis. lncRNA-ATB upregulated ZEB1 and ZEB2 by competitively binding the miR-200 family and then induced EMT and invasion. In addition, lncRNA-ATB promoted organ colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
1,322
2
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,404 publications
(1,383 citation statements)
references
References 42 publications
32
1,322
2
10
Order By: Relevance
“…11,12,28 For example, lncRNA maternally expressed gene 3 (MEG3) has been found to inhibit liver fibrosis via p53. 11 In this study, HOTAIR was found to be upregulated in HSCs in vivo and in vitro during liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,28 For example, lncRNA maternally expressed gene 3 (MEG3) has been found to inhibit liver fibrosis via p53. 11 In this study, HOTAIR was found to be upregulated in HSCs in vivo and in vitro during liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other ncRNAs, such as long intergenic non-coding RNAs (lincRNAs) and the heterogeneous group of long non-coding RNAs (lncRNAs), have also been reported to be involved in human diseases. [11][12][13] LncRNA is most commonly defined as a non-protein-coding RNA molecule longer than 200 nucleotides. Increasing evidence has demonstrated that lncRNAs are involved in a wide range of biological processes, including differentiation, proliferation, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In this, it could be analogous to other ncRNAs, such as Linc-ROR, LncRNA-ATB, and MALAT1, which stabilize mRNAs by acting as competing endogenous RNAs to sequester miRNAs and inhibit the miRNA-mediated decay of their target mRNAs. [34][35][36] Alternatively, BC200 RNA may increase the stability of S100A11 mRNA by interacting with complementary sequences. There is a putative BC200 RNA binding site between positions ¡30 and ¡15 of S100A11 mRNA relative to the start codon (C 1 would be A of the ATG codon).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are very abundant with estimates of 430 000 lncRNAs transcripts in the human genome. [71][72][73][74][75][76][77] One group of investigators estimated that there were close to 60 000 lncRNAs including 8000 oncologic lncRNAs. 74 A growing number of these lncRNAs are being isolated and characterized from thyroid and other cancers.…”
Section: Non-coding Rnas and Emt Micrornas And Emtmentioning
confidence: 99%